Stylistic Enactment in Pindar Nemean Seven (revisited) - Howie, J. G. (Hyperboreus, 2016)
I argue that in his address to Sogenes in N. 7. 70–76 Pindar excuses himself for not having addressed the young victor earlier and for having proudly said so much about his own feat of composing a myth widely acceptable in the Greek world (see 64–67a).  I further argue that Pindar, as a ﬁgurative pentathlete, swears not to have broken any rule in his throw; the risk of a foul throw had lain in his  quick tongue (72), prompting a boast in lines 64–67a about his performance. The mention of an improper exclamation in line 76 also refers to that risk of offence. However, these lines also allude to two of Sogenes’ own three victories in the pentathlon, the javelin and the wrestling, through the simile enclosed in the oath in lines 71–73 (§ 2a), and to the long jump, through a combination of suggestive wording and stylistic enactment in lines 75b–76 (§ 2b). If that is so, lines 70–76 are revealed as a piece of Pindaric virtuosity which draws the Greek language itself into a daring linguistic and conceptual feat of athleticism (§ 3).In order to provide a fuller picture of the background of this study I conclude with two Appendices, one providing examples of hyperbaton being employed by other authors for stylistic enactment (Appendix 1) and the other providing examples of other forms of stylistic enactment employed by Pindar and other authors (Appendix 2).